THE STRUCTURAL, IMPEDANCE AND DIELECTRIC A FERRITE CORE OF IRON MANGANITE AND ITS COMPOSITE - Yohanes Edi Gunanto; Henni Sitompul; Maya Puspitasari Izaak; Wisnu Ari Adi (Jurnal Sains Materi Indonesia, 2021)
THE STRUCTURAL, IMPEDANCE AND DIELECTRIC A FERRITE CORE OF IRON MANGANITE AND ITS COMPOSITE. Samples with single-phase MnFeO3 and multiphase MnFeO3/ZnFe2O4 (30/70), and MnFeO3/ZnFe2O4/LaMnO3 (30/40/30) have been successfully prepared as ferrite cores by the solid-state reaction method using high energy milling. Crystal structure, surface morphology, impedance, AC-conductivity and dielectric quantities, such as dielectric constant and dielectric loss have been studied. The crystalline structures for MnFeO3, ZnFe2O4, and LaMnO3 are hexagonal, cubic and monoclinic, The Rietveld program used for XRD analysis resulted in the composition fractions of single phase MnFeO3, multiphase MnFeO3/ZnFe2O4 (31/69), and MnFeO3/ZnFe2O4/LaMnO3 (31/40/29). The morphology of all samples has a heterogeneous shape and size with low porosity. The single-phase impedance of MnFeO3 is higher than the multiphase sample. The conductivity of the three samples has the same pattern, which is relatively constant at low frequencies and begins to increase at frequencies above 10 kHz. The dielectric constant and dielectric loss (tan ????) have high values at low frequencies, decrease exponentially with increasing frequency and are relatively fixed at high frequencies.